SISTEM KEAMANAN DATA DENGAN METODE CRYPTOGRAPHY - Peniarsih Peniarsih (JURNAL MITRA MANAJEMEN, 2012)
AbstractFor data protection is important enough there is no other way but to use a special programprotection / encryption of data. When this has been a lot of outstanding special program dataprotection either freeware, shareware, and commercial is very good. In general, these programsnot only provide a single method alone, but some kind so that we can choose who we think is themost secure. One method is public key encryption criptography. Cryptography is a science or artof secure messaging and performed by criptographer. Criptography Public Key cryptography isdone by combining the two related keys called a key pair of public and private keys. Both keysare created at the same time and relate it mathematically.Semetrik algorithm is a type of encryption algorithms are the most common. This algorithm iscalled symmetric because the same key used for encryption and decryption. Unlike the keys usedin public key algorithms, symmetric key that is used on keys typically change often. Whencompared with the public key algorithms, symmetric key algorithms are very fast and thereforeare more suitable when used to encrypt the data is very large. Modern cryptographic protocolsthat incorporate many current public key algorithm with a symmetric algorithm to obtain theadvantages of each algorithm.